Perilaku Beberapa Klaster Masyarakat Di Sekitar Sungai Tuk Terhadap Air Limbah Domestik - Lutfi Aris Sasongko (Universitas Wahid Hasyim, 2011)
Water is the most precious natural material. Water quality is strongly influenced by the social environment such as population density and social density. Tuk River is one of the Kali Garang River tributary that crossed markets and residential areas that have the potential for contamination by domestic waste. Region through which the river, these include the Sampangan Village and Bendan Ngisor Village Gajahmungkur District. The focus of this research is the behavior of a few clusters of communities around the Tuk River related domestic waste water disposal in terms of aspects of knowledge, attitude and action. Primary data were collected by conducting interviews using the questionnaire tool. Secondary data in the form of a general description of the Tuk River and statistical data obtained from relevant agencies. The populations in this study were residents in the Bendan Ngisor Village and Sampangan Village. The design of the study sample was selected proportionally based on location of residence. The numbers of samples taken from each cluster of residence and selected purposively. Selected sample is the sample that living near the Tuk River and dispose of domestic waste water into the Tuk River. The data have been collected were analyzed by analysis of frequency tables, cross tabulation and simple correlation analysis. The results showed that the behavior of middle settlement cluster of respondents to domestic waste water on aspects of knowledge and attitude better than any other settlement clusters. However, in action aspect, respondents in small settlement cluster better than the other two clusters of settlements. The level of education has a fairly good correlation in the attitudes of respondents, but still less correlated to the knowledge and actions in respondent’s domestic waste water disposal into the river bodies. The fact that encountered in the field, indicating that the action of respondents in addition to dispose of domestic waste water is influenced by the knowledge and attitudes are also influenced by the existing drainage system in the neighborhood. Keywords: Tuk River, domestic waste water